Nutritional value and contamination testing assistance for the improvement of the processed food products quality - Syarif Hamdani; Adang Firmansyah; Muhammad Ismail Faruqi; Dewi Astriany; Sri Gustini; Wiwin Winingsih; Melvia Sundalian; Nur Asni Setiani; Putri Afiyanti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are one of the business sectors driving the country's economy. MSMEs produce many quality products that can compete in the market, where one of the products that is marketed quite a lot is food products. Several MSMEs in the Purwakarta Regency area have not included information on nutritional value and contamination on labels or packaging so these products cannot be widely marketed or traded in official stores and can only be marketed in their production areas. The Community Service activities carried out aim to carry out nutritional value and contamination tests, followed by improving product quality through workshops and mentoring. The food products targeted are simping and instant turmeric drinks produced by MSMEs in Pondoksalam District, Purwakarta Regency. Laboratory test results show that instant turmeric does not meet several SNI standard parameters, so quality improvement is still needed to be able to adapt it to become a product that meets standards. The results of the questionnaire show that several MSME owners in the Purwakarta area have a poor understanding of food product quality standards and ways to improve them. The coaching program for community service activities shows an increase in knowledge and understanding so that food products from Purwakarta MSMEs are expected to meet product quality standards in the future.